A climatic control on reorganization of ocean circulation during the mid-Cenomanian event and Cenomanian-Turonian oceanic anoxic event (OAE 2): Nd isotope evidence - Zheng, X; Jenkyns, H; Gale, A; Ward, D; Henderson, G (Geological Society of America, 2017)
Although ocean circulation plays a vital role in the climate system, its response to major carbon-cycle perturbations during the mid-Cretaceous, including Mid-Cenomanian Event I (MCE I) and Cenomanian–Turonian oceanic anoxic event (OAE 2), is poorly constrained. Here we present Nd-isotope evidence for episodic increases in the influence of boreal seawater in the European epicontinental sea during MCE I. The start of this circulation reorganization lagged the onset of the δ13C positive excursion defining MCE I. This sequence of change is similar to that observed during OAE 2 in the same area, showing a consistent response of regional circulation to changes in the global carbon cycle. Brief intervals of invasion of boreal fauna to mid-latitude seas, two during MCE I and one during OAE 2 (Plenus Cold Event), always started after the influence of boreal seawater was enhanced, implying a slower biological response to climate cooling, rather than passive transport of fauna by boreal waters. The lack of an Nd-isotope positive excursion in our record across MCE I supports a volcanic origin for prominent increases in seawater Nd-isotope values found in the European epicontinental sea and tropical Atlantic during OAE 2. The observed tight circulation–carbon cycle coupling may help the upper ocean replenish nutrients from deep waters and/or volcanic sources, providing a critical feedback allowing continuation of MCE I and OAE 2 over long durations.